Mid-term follow-up of percutaneous access for standard and complex EVAR using the ProGlide device. Issue 3 (June 2022) - Bradley, N.A.; Orawiec, P.; Bhat, R.; Pal, S.; Suttie, S.A.; Flett, M.M.; Guthrie, G.J.K.
Abstract: Objectives: Endovascular Aneurysm Repair is an established treatment for abdominal aortic aneurysm which requires arterial access via the groin. Most centres perform percutaneous ultrasound-guided access into the common femoral artery for delivery of the stent graft. The profile of endovascular devices necessitates large sheath sizes, therefore formal closure of the arterial puncture site is required. Various percutaneous devices are available, with data lacking on efficacy and mid-term safety profile. We present outcomes from a single centre with the Perclose ProGlide™ (Abbott Vascular Devices, CA, USA) suture-mediated system, using the well described "pre-close" technique. Materials & methods: Data were collected from operative records and electronic medical records. Patients undergoing standard (EVAR) or complex (F/B-EVAR) aneurysm repair between March 2015 and September 2019 were included. Complications were recorded per-patient and per-groin procedure. Results: 266 patients were included; 182 (68.4%) standard infrarenal EVAR, 84 (31.6%) F/B-EVAR. There were a total of 484 groin procedures performed. Intraoperative Perclose ProGlide™ success was 98.1% (per patient) or 99.0% (per groin procedure). 30-day groin complication rate was 6.1% (per patient) or 3.1% (per groin procedure). There were no pre- or peri-operative factors which predicted the occurrence of groin complications. The rate of groin complications was not related to sheath size. Conclusions: Our data support the use of percutaneous access with a pre-close technique for a variety of endovascular aneurysm repair procedures with both large- and small-bore access. The Perclose ProGlide™ system provides excellent mid-term complication-free and reintervention-free outcomes for groin procedures. Highlights: Percutaneous access for EVAR requires closure of access site arteriotomies. Complex EVAR requires larger sheath sizes which may be more challenging to close. The ProGlide device provides safe early and mid-term access site closure. The totally percutaneous approach may reduce length of stay versus open access.